(untitled) (Fiep Bulletin - online, 2014)
The objective of this study was to describe the overweight and obesity prevalence among students from the central region of the state of Rio Grande do Sul and to verify possible association between the Body Mass Index (BMI) and the Health-Related Physical Fitness scores (AFRS). 1423 students (54.1% boys and 45.9% girls) with ages ranging from 7 to 17 years from schools of three cities at the inland of the state of Rio Grande do Sul were evaluated. Overweight and obesity were defined based on the BMI equal to or greater than 25 and 30 kg/m², adapted for age and gender according to recommendations from Cole et al (2000). The AFRS was evaluated based on the 9-minute, Abdominal and Flexibility tests. For the statistical analysis, the "t" Student test (to verify differences between genders) and the Chi-square test (to verify possible differences between prevalences and association between BMI and the AFRS scores) were applied. Linear regression was used to verify the existence of linear relation between BMI and age. Overweight and obesity prevalences of 16.8% and 4.6% were found, respectively. Boys presented higher prevalences of overweight (17.9% and 15.5%) and obesity (5.7% and 3.3%), respectively, when compared to girls, and this difference was statistically significant (p<0.05). The age range of 10 - 14 years presented the highest percentage of overweighed and obese individuals. Linear regression indicated the existence of linear relation between BMI and age. An association between overweight/obesity in the 9-minute and Abdominal tests was found. One may conclude that the overweight and obesity prevalence in the region investigated is higher among boys. The highest overweight prevalence was found at the 10 - 14 age range. Overweighed and obese children presented trend to obtain indexes below recommended values for the AFRS tests.